Tinjauan Fikih Ekonomi terhadap Pertanggungjawaban atas Harta dalam Bisnis Kontemporer - Lara Aziza Putri; Zainuddin; Abdul Kahfi; Erliati Siregar; Anggi Kartika N (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
The development of contemporary business presents new challenges in managing and accounting for wealth, particularly within the context of Islamic economics. This study aims to explore the concept of wealth accountability in Islamic economic jurisprudence (fiqh) and its relevance to modern business practices. Using a descriptive qualitative approach and literature review method, the research analyzes both classical and contemporary sources in Islamic law and economics. The findings show that key Sharia principles such as trust, transparency, justice, and contractual clarity remain highly relevant in digital business, fintech services, and collective investments. With its normative flexibility, Islamic economic fiqh proves capable of adapting to today’s economic dynamics while upholding core Sharia values. The study underscores the need to revitalize fiqh principles in addressing digital economic growth and globalization. Thus, Islamic economic jurisprudence has strong potential to serve as both an ethical and practical foundation for fair, transparent, and sustainable business practices.